Assessment of the Pelangwot-Sedayu Lawas Floodway Capacity for Managing Floods in the Lower Bengawan Solo River - Amalia, Dewi; Sumiadi, Sumiadi; Dermawan, Very; Ivan, Hans (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
The Pelangwot-Sedayu Lawas floodway is the main infrastructure for a flood control system in the Lower Bengawan Solo. However, frequent flooding still occurs in the Turi and Kali Tengah subdistricts of Lamongan Regency. Therefore, the number of emergency gates in the floodway has been increased. An important aspect of this flood control is ensuring that, despite the increase in capacity of the Pelangwot-Sedayu Lawas floodway gates, the water surface elevation at Pelangwot does not lead to overflow and that the floodway channel from Pelangwot to Sedayu Lawas effectively conveys the maximum discharge. This study aims to assess the capacity of the emergency gates to convey a flood discharge of 1000 m³/s and the capability of the floodway channel to accommodate flows from both the emergency gates and outlet of Jabung Retarding Basin, which amounts to 1140 m³/s. The analysis of floodway capacity involves calculating the discharge through five floodway gates and simulating the floodway channel to manage flood discharge using the HEC-RAS 5.0.7 software. Results indicate that with a gate opening of 5 m, the five gates can discharge 1000 m³/s at a water surface elevation of +7.03 masl, reducing floods by 32.09%. To improve capacity, the embankment must be elevated by 1.0 meters, with a crest width of 4.00 meters along the left bank for 4.4 km and the right bank for 4.35 km. These modifications are essential to enhance flood management and protect downstream areas.